Postembryonic lineages of the Drosophila brain: II. Identification of lineage projection patterns based on MARCM clones - Wong, Darren C. (2013)
The Drosophila central brain is largely composed of lineages, units of sibling neurons derived from a single progenitor cell or neuroblast. During the early embryonic period neuroblast generate the primary neurons that constitute the larval brain. Neuroblasts reactivate in the larva, adding to their lineages a large number of secondary neurons which, according to previous studies in which selected lineages were labeled by stably expressed markers, differentiate during metamorphosis, sending terminal axonal and dendritic branches into defined volumes of the brain neuropil. We call the overall projection pattern of neurons forming a given lineage the “projection envelope” of that lineage. By inducing MARCM clones at the early larval stage, we labeled the secondary progeny of each neuroblast. For the supraesophageal ganglion excluding mushroom body (the part of the brain investigated in the present work) we obtained 81 different types of clones, Based on the trajectory of their secondary axon tracts (described in the accompanying paper), we assigned these clones to specific lineages defined in the larva. Since a labeled clone reveals all aspects (cell bodies, axon tracts, terminal arborization) of a lineage, we were able to describe projection envelopes for all secondary lineages of the supraesophageal ganglion. This work provides a framework by which the secondary neurons (forming the vast majority of adult brain neurons) can be assigned to genetically and developmentally defined groups. It also represents a step towards the goal to establish, for each lineage, the link between its mature anatomical and functional phenotype, and the genetic make-up of the neuroblast it descends from.